2015
DOI: 10.18549/pharmpract.2015.01.533
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral anti-diabetic drugs among patients attending a Ghanaian teaching hospital

Abstract: *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 15 publications
(18 reference statements)
5
49
4
Order By: Relevance
“…It was revealed that majority of the participants adhered correctly to their medication regimen as found among other study participants [15,16]. The finding however contradicted with a research conducted at Korle-bu Teaching Hospital in Ghana in which smaller number of study participants adhered correctly to their medication regimen [17]. In this study most of the respondents asserted they had never missed a single dose of their medication over the past week which was similar to findings by other authors [16].…”
Section: Discussionsupporting
confidence: 48%
“…It was revealed that majority of the participants adhered correctly to their medication regimen as found among other study participants [15,16]. The finding however contradicted with a research conducted at Korle-bu Teaching Hospital in Ghana in which smaller number of study participants adhered correctly to their medication regimen [17]. In this study most of the respondents asserted they had never missed a single dose of their medication over the past week which was similar to findings by other authors [16].…”
Section: Discussionsupporting
confidence: 48%
“…This has created a gap in knowledge in the context of T2DM from an Afrocentric perspective. While medications for managing T2DM in Ghana are readily available, adherence to these medications is still not optimal [35,36]. Thus, the information from this study will facilitate context-specific understanding of the problem from a psychosocial perspective so that culturally appropriate adherence solutions can be instituted.…”
Section: Introductionmentioning
confidence: 98%
“…5 A research developed in Ghana has indicated that 38.5% of the participants adhered to the regular use of the OAD. 4 Other national research studies that analyzed adherence to antihypertensive treatment and to OAD have reported an adherence of 47% and 60%, respectively. 6,7 The prevalence of non-adherent individuals to the established therapy may reach an irreversible gravity, and increased rates of morbimortality and of health public expenses for the treatment.…”
Section: Introductionmentioning
confidence: 98%
“…2 However, evidence points to low adherence of people with T2DM in following the established medication therapy. 3,4 Low or non-adherence to the treatment of chronic diseases such as diabetes ranges from 6% to 55%. 5 The literature shows that individuals with lower schooling and younger people present an ineffective adherence to the treatment.…”
Section: Introductionmentioning
confidence: 99%